Public policies for mental health of schoolchildren: Prevention of child anxiety - Lima, Ana Flávia Freire Tavares; Cruz, Elisian Macêdo Fechine da; Alves , Sabrina Alaide Amorim; Jastrow, Juliana Maria Bello; Elbani, Ana Carolina Lopes; Bezerra, Italla Maria Pinheiro (Seven Editora, 2023)
The study aimed to discuss public policies in the prevention of childhood anxiety and impacts on the teaching-learning process. This is a theoretical essay with a reflective nature. The proposed reflections were based on relevant international and national literature. Currently, increases in Anxiety Disorders have been observed in school-aged children, impairing their health, social relationships and learning performance. In this context, it is believed that the development of public policies is presented as strategies for promoting mental health, especially in the school context. DOI:https://doi.org/10.56238/globalhealthprespesc-005